Cardiac health knowledge and misconceptions among nursing students: implications for nursing curriculum design - Susan Ka Yee Chow; Yuen Yee Chan; Sin Kuen Ho; Ka Chun Ng (BMC, 2017)
Abstract Background Cardiac misconceptions are common among healthcare professionals. The development of professional knowledge is considered an essential component of nursing education. Nurses, regardless of their grade, skills, and experience, should be updated with information so as to be able to rectify their misconceptions, as these could affect patient health outcomes. As the literature evaluating the cardiac knowledge and misconceptions of nursing students is sparse, a study of the subject seems warranted. Methods A cross-sectional sample survey was used to study the cardiac knowledge and cardiac misconceptions of nursing students in Hong Kong. The study sample included 385 senior nursing students from three universities. Their level of knowledge of cardiac disease was assessed using the modified Coronary Heart Disease Knowledge Test. The York Cardiac Beliefs Questionnaire (YCBQv1) was used to examine cardiac misconceptions. Results The scores for the nursing students' level of knowledge were diverse. Their mean score in the Cardiac Knowledge Test was 12.27 out of 18 (SD 2.38), with a range of 2-17. For cardiac misconceptions, their mean score in the YCBQv1 was 6.98 out of 20 (SD 2.84), with a range of 0-14. A negative correlation, r = −0.33 was found among students with more knowledge and fewer misconceptions. (p < 0.001). The Chi-square tests found some associations between the students' experiences of caring for cardiac patients and misconceptions about stress and physiology. Conclusions The results of our analyses indicate a diversity in levels of knowledge among the nursing students. Students with higher scores in cardiac knowledge did not necessarily have fewer misconceptions. There were associations between the students' misbeliefs and their caregiving experiences with cardiac patients. This study presents a framework for designing the contents of cardiac nursing programmes and is a starting point for promoting research on misconceptions held by undergraduate nursing students. A new paradigm of teaching should include inputs from both perspectives to help students to make critical use of theoretical knowledge to rectify their misconceptions and pursue excellence in the working world.